Sosyal Bilgiler Öğretmen Adaylarının 21. Yüzyıl Becerileri Yeterlik Algıları ile Yaşam Boyu Öğrenme Eğilimlerinin Çeşitli Değişkenler Açısından İncelenmesi - Aksüt, Selda; Ezer, Feyzullah (Kahramanmaras Sutcu Imam University, 2025)
Araştırmanın amacı, sosyal bilgiler öğretmen adaylarının 21. yüzyıl becerileri yeterlik algıları ile yaşam boyu öğrenme eğilimlerini çeşitli değişkenler açısından incelemektir. Araştırmanın örneklemini, 2021-2022 eğitim öğretim yılında Adıyaman, Ankara, Balıkesir, Bursa Uludağ, Çukurova, Erzincan Binali Yıldırım, Fırat, Gazi, Kırşehir Ahi Evran, Marmara, Ondokuz Mayıs, Pamukkale, Recep Tayyip Erdoğan, Sivas Cumhuriyet ve Süleyman Demirel Üniversitelerinin Eğitim Fakültesi Sosyal Bilgiler Eğitimi Bilim Dalında 1., 2., 3. ve 4. sınıfta öğrenim gören 2850 öğretmen adayı oluşturmaktadır. Örneklem belirlenirken tabakalı örnekleme yöntemi kullanılmıştır. Araştırma nicel araştırma yöntemlerinden, betimsel tarama modeli ile yürütülmüştür. Araştırmada verilerin analizi için aritmetik ortalama, standart sapma, bağımsız örneklemler t-testi ve tek yönlü varyans analizi kullanılmıştır. Araştırma sonucunda, sosyal bilgiler öğretmen adaylarının, 21. yüzyıl becerileri yeterlik algıları ile yaşam boyu öğrenme eğilimlerinin yüksek düzeyde olduğu, üniversite ve sınıf düzeyi değişkenine göre anlamlı farklılık gösterdiği fakat cinsiyet değişkenine göre anlamlı farklılık göstermediği belirlenmiştir. 21. yüzyıl becerileri yeterlik algıları ile yaşam boyu öğrenme eğilimlerini geliştirmeye yönelik üniversitede yapılması düşünülen etkinlikler öğretmen adaylarının ilgi ve ihtiyaçları doğrultusunda planlanmalı ve bu etkinliklere katılmaları için öğretmen adayları motive edilmelidir.

The aim of the research is to examine social studies teacher candidates’ 21st century skills competency perceptions and lifelong learning tendencies in terms of various variables. The sample of the study consisted of 2850 first, second, third, and fourth-year pre-service social studies teachers studying in the Faculty of Education in Adıyaman, Ankara, Balıkesir, Bursa Uludağ, Çukurova, Erzincan Binali Yıldırım, Fırat, Gazi, Kırşehir Ahi Evran, Marmara, Ondokuz Mayıs, Pamukkale, Recep Tayyip Erdoğan, Sivas Cumhuriyet and Süleyman Demirel University in the 2021-2022 academic year. While determining the sample of the research, stratified sampling method, was used. The research was conducted with the descriptive survey model, one of the quantitative research methods. For the analysis of the data in the research arithmetic mean, standard deviation, independent samples t-test and one-way analysis of variance were used. As a result of the research, it was determined that social studies teacher candidates’ 21st century skills proficiency perceptions and lifelong learning tendencies were at a high level, and there were significant differences according to the university and grade level variable, but there was no significant difference according to the gender variable. Activities planned to be held at the university to develop 21st century skills competency perceptions and lifelong learning tendencies should be planned in line with the interests and needs of prospective teachers, and prospective teachers should be motivated to participate in these activities.

The aim of the research is to examine social studies teacher candidates’ 21st century skills competency perceptions and lifelong learning tendencies in terms of various variables. The sample of the study consisted of 2850 first, second, third, and fourth-year pre-service social studies teachers studying in the Faculty of Education in Adıyaman, Ankara, Balıkesir, Bursa Uludağ, Çukurova, Erzincan Binali Yıldırım, Fırat, Gazi, Kırşehir Ahi Evran, Marmara, Ondokuz Mayıs, Pamukkale, Recep Tayyip Erdoğan, Sivas Cumhuriyet and Süleyman Demirel University in the 2021-2022 academic year. While determining the sample of the research, stratified sampling method, was used. The research was conducted with the descriptive survey model, one of the quantitative research methods. For the analysis of the data in the research arithmetic mean, standard deviation, independent samples t-test and one-way analysis of variance were used. As a result of the research, it was determined that social studies teacher candidates’ 21st century skills proficiency perceptions and lifelong learning tendencies were at a high level, and there were significant differences according to the university and grade level variable, but there was no significant difference according to the gender variable. Activities planned to be held at the university to develop 21st century skills competency perceptions and lifelong learning tendencies should be planned in line with the interests and needs of prospective teachers, and prospective teachers should be motivated to participate in these activities.
Examining Social Studies Teacher Candidates’ 21st Century Skills Efficacy Perceptions and Lifelong Learning Tendencies in Terms of Various Variables
Keywords: Basic Training (Other); Temel Eğitim (Diğer)